Properties of the organic matter of the Bazhenov suite in the Yugansk Megadepression based on Rock-Eval Pyrolysis; IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development 7–11 April 2014, Tomsk, Russia - Goncharov I. V. Ivan Vasilyevich (Petroleum Geology, 2014)
Title screen